1992
DOI: 10.1002/ajim.4700220308
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity in retired coke oven plant workers

Abstract: The effect of past occupational exposure on morbidity was studied in 354 coke oven workers in Lorraine Collieries (France) who retired between 1963 and 1982, and were still alive in 1988; 96% of them participated in this study. Occupational exposure to respiratory hazards during the working life was retraced for each subject. No significant association between the occupational exposure and the frequency of ischemic cardiopathies, arterial hypertension, gastro-duodenal ulcers, and respiratory symptoms was revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Smoking did not differ significantly between each exposed group and the non-exposed group. 17 37 231…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking did not differ significantly between each exposed group and the non-exposed group. 17 37 231…”
Section: Resultsmentioning
confidence: 99%
“…All types combined 1-4 (1-8) 23-8 (8-2) 23-4 (7 9) 23-1 (9-9) 23 1 (9 1) 17 Comparison of means, comparison of frequencies, and homogeneity test between each exposed group and the non-exposed group (except for the duration of exposure where the difference is obvious). *p < 0 05.…”
Section: Resultsmentioning
confidence: 99%
“…However, they found an increased frequency of respiratory symptoms associated with the increased degree of bronchial hyperreactivity in coke oven workers. Mayer et al 13 reported the prevalence of cough, phlegm, wheeze, bronchitis, and exertional dyspnea in 354 retired coke oven workers in 1992. The effects of occupational exposure on these symptoms were not established in their study.…”
Section: Discussionmentioning
confidence: 98%